Lab-on-a-chip for rapid electrochemical detection of nerve agent Sarin - Tan, Hsih Yin (2016)
This paper reports a lab-on-a-chip for the detection of Sarin nerve agent based on rapid electrochemical detection. The chemical warfare agent Sarin (C4H10FO2P, O-isopropyl methylphosphonofluoridate) is a highly toxic organophosphate that induces rapid respiratory depression, seizures and death within minutes of inhalation. As purified Sarin is colourless, odourless, water soluble and a easily disseminated nerve agent, it has been used as a weapon in terrorist or military attacks. To ascertain whether potable water supplies have been adulterated with this extremely potent poison, an inexpensive, sensitive and easy to use portable test kit would be of interest to first responders investigating such attacks. We report here an amperometric-based approach for detecting trace amounts of Sarin in water samples using a screen-printed electrode (SPE) integrated in a microfluidic chip. Enzymatic inhibition was obtained by exposing the immobilised biosensor in the microfluidic platform to Sarin in water samples. With the aid of cobalt phthalocyanine modified SPE, the device could detect Sarin at part-per-billion levels with concentration as low as 1 nM. The detection method reported here represents a significant improvement over the authors’previous optical-based detection method.